ANALISIS MANAJEMEN MODAL KERJA ( STUDI KASUS PADA PT BANK TABUNGAN NEGARA Tbk) - LIKUPANG, YOKSAN; PELLENG, FRENDY; TAMPI, DOLINA (JURNAL ADMINISTRASI BISNIS (JAB), 2016)
Working capital management contains two meanings, namely gross working capital which is the total of current assets and net working capital as the difference between current assets less current liabilities. The goal of working capital management is to manage current assets to guarantee the amount of net working capital are acceptable which assure the level of liquidity of the enterprise.The purpose of research is to find out how the implementation of working capital management at the State Savings Bank Tbk branch of Manado. The method used is descriptive method using a quantitative approach to the analysis of financial statements, data and data sources obtained from PT. Bank Tabungan Negara, Tbk Branch Manado.The results showed that, Ratio of Total Assets to net working capital pads in 2013 amounted to 9.089 and in 2014 amounted to 12.959. This indicates that the ratio of total assets to working capital secured by current assets and current liabilities; Ratio Current Liabilities towards working capital PT. Bank Tabungan Negara, Tbk in 2013 amounted to 8.288 and pads in 2014 amounted to 11.865. This shows that the ratio of Current Liabilities PT. Bank Tabungan Negara, Tbk is stable; Working Capital Turnover Ratio (Revenues to net working capital ratio) in 2013 amounted to 8.008 and in 2014 amounted to 10.941. That means there are increased every year from 2013 to 2014 by a margin of 2.933. This increase was due to an increase in net working capital.It is recommended that PT. Bank Tabungan Negara, Tbk Branch Manado always pay attention to working capital management in particular has always perform financial statement analysis, among others, the calculation; total assets to net working capital ratio, current liabilities to net working capital ratio, working capital to net revenues ratio, so that the bank's management to answer the challenges of the banking world today is increasingly complex. Also regarding the employee's performance and strategy planning and development resources to the challenges the banking world today is increasingly complex, it is necessary diperhatkan by the Bank management .Keywords: total assets, current liabilities, turnover working capital.